Eksperimental'noe obosnovanie Effektivnosti metodiki obycheniya yunykh bortsov tekhniko-takticheskim deistviyam s ispol'zovaniem tekhnicheskikh sredstv - Pavlov, A. E. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of this study was to develop the basic ways of perfection of educational methodic for young wrestlers. There special educational methodic was used in the experiment, in which technical resources were applied. An orientation of influences on physical and special motor preparedness of young wrestlers considerably changes. But their technical preparedness is exposed to especially essential influence. The efficiency of application of separate expedients and conducting of fights. It is visible both in marks and in total of the used appreciated technical-tactical actions.